Acid base disturbances in the Intensive Care Unit of “Víctor Lazarte Echegaray” hospital: incidence, length of stay and mortality - Arroyo Sánches, A. (2024)
Introducction: Acid-Base(A - B) alterations are a frequent problem of patients in Intensive Care Units (ICUs); therefore, its important to evaluate morbidity and mortality of this pathology in the ICUs Objetive: to determine the incidence of Acid Base (A-B) disorders and their relationship with lenght of hospitalization and mortality in the Intensive Care Unit (ICU). Material and methods: Results: during the period of the study of 131 pacients were hospitalized. In 100 the mean age was 66.9 ± 18,9 years, the mean APACHE II score was 18,07 7,62 points; the mean hospital stay in ICU was 6,42 ± 7,78 days and the mortality within the ICU was 24% (24 patients). The gasometric mean values were pH 7,39 ± 0.11, paCO2 37.79 ± 10,08 mmHg. BE- 1,40 ± 6,93 mEQ/Lt. The more frequent A-B disorders were metabolic acidosis (21%) and mixed primary metabolic alterations (20%). No A-B disorder was found in 14% of the patients. The A-B disorders with longer hospital stays in ICU were respiratory acidosis (9,14 6,1 days) and mixed primary metabolic alterations (9,75 ± 8,0 days). Greater mortality was observed in the groups with metabolic acidosis (28,6%) and respiratory acidosis (27%). Conclusions: the incidence of A-B disorders was high (86%). Metabolic alterations (acidosis and mixed) had a greater incidence; the respiratory alterations (acidosisand mixed) were associated with longer ICU stays and the acidoses (metabolic and respiratory) were associated with greater mortality.